An unwanted guest [large type] - Lapeña, Shari, 1960- (Random House Large Print, 2018)
A weekend retreat at a cozy mountain lodge is supposed to be the perfect getaway . . . but when the storm hits, no one is getting away. It's winter in the Catskills and Mitchell's Inn, nestled deep in the woods, is the perfect setting for a relaxing--maybe even romantic--weekend away. It boasts spacious old rooms with huge woodburning fireplaces, a well-stocked wine cellar, and opportunities for cross-country skiing, snowshoeing, or just curling up with a good murder mystery. So when the weather takes a turn for the worse, and a blizzard cuts off the electricity--and all contact with the outside world--the guests settle in for the long haul. Soon, though, one of the guests turns up dead--it looks like an accident. But when a second guest dies, they start to panic. Within the snowed-in paradise, something--or someone--is picking off the guests one by one. And there's nothing they can do but hunker down and hope they can survive the storm.